LEARNING STYLE IN LANGUAGE LEARNING CLASSROOM - Masruddin Masruddin (Institut Agama Islam Negeri Palopo, 2018)
This article describes the concept of learning style and the learners’ characteristic of each learning style of students in language learning. In the first part of this article the writer describes the learning style. Then the writer will related the learning style to language acquisition. There are 3 types of language learning style described by Tekavcic and Dimovski namely visual, auditory and tactile funtions of someone in processing information. The three main types of learning style are not absolute, of course. Many learners learn through a variety of senses. Certain students might equally be strong in the three perceptual modalities, or in two perceptual modalities of either combination